University Students’ Understanding on Cultural Activities in American Culture Class - Maryani Maryani; Lewinna Christiani Aguskin (Lingua Cultura, 2018)
This research examined university students’ cultural understanding based on cultural activities that they had experienced. The data were gathered from 20 Indonesian university students who were attending American culture class through a questionnaire and ten learning logs. These students had experienced four different types of cultural activities. They were asked to share the experiences they have had regarding the cultural activities in the questionnaire and their gained knowledge related to each cultural activities in the learning log. The qualitative data were analyzed manually and classified into tables. The findings were used to explore student’s understanding of the use of cultural activities in learning and understanding American culture. In conclusion, the students gain deeper understanding after experiencing the cultural activities regarding American culture. The cultural activities practiced in this research can be used and developed for other subjects to enhance teaching and learning process in the classroom, especially to increase students’ comprehension of the particular subjects.